The Effect of Work-Life Balance and Work Environment on Employee Performance with Job Satisfaction as a Mediating Variable - Subroto, Setyowati; Lubis, Alifah Lettiane Virainy; Sono, Mohammad Gifari (Westscience Press, 2025)
This study examines the effect of work-life balance and work environment on employee performance with job satisfaction as an intermediary variable. Using a quantitative approach, data were collected from 180 employees through a structured questionnaire measured on a five-point Likert scale. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results reveal that work-life balance and work environment both have significant positive effects on job satisfaction, with the work environment showing the stronger influence. Job satisfaction, in turn, has a very strong positive effect on employee performance. Mediation analysis confirms that job satisfaction fully mediates the effect of work environment on performance and partially mediates the effect of work-life balance on performance. These findings suggest that organizational performance can be improved by creating a supportive work environment and promoting work-life balance, with job satisfaction serving as the key mechanism that drives employee productivity.